A compressed image encryption algorithm leveraging optimized 3D chaotic maps for secure image communication - Tiwari, Akshat; Diwan, Prachi; Diwan, Tarun Dhar; Miroslav, Mahdal; Samal, S P (Scientific reports, 2025)
In today's digital age, sensitive multimedia informations are transmitted over public networks that are vulnerable to unauthorized access and data tampering. This motivates more robust encryption methods to combat such security threats. In this paper, a chaotic map-based encryption technique is presented as a solution to these issues. The proposed algorithm termed as OptiSecure-3D presents optimized parameter-based 3D chaotic maps for image encryption. The method integrates three primary components: stacked autoencoder (SAE), optimized parameter-based chaotic mapping, and encryption/decryption module, to ensure robust and secure encryption of images. The result evaluated the proposed OptiSecure-3D image encryption algorithm with a randomness test, pixel adjacency correlation test, and differential analysis. The mean entropy was approx. 7.9 and the mean number of pixels changing rate (NPCR) was approx. 99.8, unified average changing intensity (UACI) was approx. 33.46. Moreover, the OptiSecure-3D algorithm also investigated the result under noise attacks and shows better cryptanalysis results as compared to comparative state-of-art models. The findings suggest that our chaotic map-based encryption technique not only provides an effective solution to the security vulnerabilities of digital image transmission but also enhances the overall reliability of multimedia communication systems. This paper presents a significant advancement in the field of secure image encryption to meets the increasing demands for data security in modern digital communication networks.
Keywords: Image encryption; Compressed encryption; Chaotic maps; Optimization; Secure communication